The role of resilience (adversity intelligence) and creativity in mathematics learning - Suhendri, Huri (Unnes Journal of Mathematics Education, 2018)
This study aims to analyze and prove the existence of resilience influence and creativity to the ability of problem solving in mathematics. The method of study used is survey method with correlational analysis. The population of this study is all students of class X SMK Kharismawita 2, South Jakarta. While the sample is 30 students class X SMK Kharismawita 2, South Jakarta in the academic year 2017/2018. Further, the instruments of data collection consisted of: a questionnaire about resilience and creativity, and a written test of mathematics subjects. The requirements of data analysis consist of: normality, linearity, and multi-collinearity test. The result of three data analysis requirement test obtained by conclusion that the three groups of data come from normal distributed population, the two regression models which are formed are in linear pattern, and there is no relation between the independent variables. Further the hypothesis test is done by correlation and regression test. Eventually, from the results of hypothesis test and analysis, it can be concluded that there is influence of resilience and creativity to the problem solving ability in mathematics. It means that resilience variable and creativity play a role in mathematics learning, which affect the problem solving skills of mathematics. Thus, in the learning, teachers focused on the factors of resilience and creativity of learners and made efforts to improve both of these factors through interesting math learning